Penguatan Branding Digital Sanggar Seni Cahya Art Baliqui melalui Pengembangan Website Profile Berbasis Vercel - Ni Wayan Nanik Suaryani Taro Putri; Anak Agung Gede Adi Mega Putra; I Made Rama Dwijaya; I Putu Gunartajaya; I Wayan Abdi Manik Kesawa; I Made Aldi Wira Kusuma; I Gede Galang Raka Raditya (AJAD : Jurnal Pengabdian kepada Masyarakat, 2026)
Conventional promotional limitations hinder the visibility of Sanggar Seni Cahya Art's Baliqui in preserving culture during the digital era. This Community Service (PKM) project aims to strengthen the partner's digital branding by developing a Vercel-based website profile. The implementation method adopts a Design Thinking framework integrated with a User-Centered Design (UCD) approach. Google Lighthouse audit results showed a perfect SEO score (100%), while GTmetrix testing achieved a Grade A with a 100% performance score. Beyond the technical figures, the real impact is reflected in the partner's positive response — stating that the website's presence significantly increases the studio's professionalism and facilitates public access to information. These results confirm that a professional, fast, and low-maintenance system infrastructure can serve as an effective promotional solution without burdening the partner with complex technical upkeep.